1995
DOI: 10.1037/1064-1297.3.4.432
|View full text |Cite
|
Sign up to set email alerts
|

A review of the effects of opioids on psychomotor and cognitive functioning in humans.

Abstract: The literature on the effects of opioids on psychomotor and cognitive functioning in humans is evaluated. Some studies have examined the acute and chronic effects of various opioids on different subject populations. In addition, epidemiologic studies have examined the neuropsychological functioning and the risk of accidents for persons who have (or have had) opioids in their systemic circulation. In general, it appears that some opioids (mixed agonist–antagonists) more than others (morphine or codeine) impair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(120 citation statements)
references
References 184 publications
(374 reference statements)
4
114
0
2
Order By: Relevance
“…A study of cancer patients taking stable, long term opioid therapy compared with a group taking no opioids demonstrated no significant difference in functions related to driving ability (32). This observation has been duplicated in subsequent studies (33)(34)(35)(36)(37)(38). Cognitive deficits in opioid-treated patients are more often due to the concurrent use of sedative medications such as benzodiazepines.…”
Section: Side Effectsmentioning
confidence: 52%
“…A study of cancer patients taking stable, long term opioid therapy compared with a group taking no opioids demonstrated no significant difference in functions related to driving ability (32). This observation has been duplicated in subsequent studies (33)(34)(35)(36)(37)(38). Cognitive deficits in opioid-treated patients are more often due to the concurrent use of sedative medications such as benzodiazepines.…”
Section: Side Effectsmentioning
confidence: 52%
“…8 Opioid-related drug overdoses are becoming increasingly prevalent, amounting to more than 40% of deaths due to drug overdoses in the United States. 1 Opioids can interfere with attention and impair reaction time, 9,10 leading to concerns regarding impaired driving performance. However, 2 small randomized controlled trials of driving simulations found no significant effect of opioids on driving performance, reaction time, or cognition, 5,6 although 1 study suggested that patients receiving opioids experienced reduced alertness and increased sedation while driving.…”
mentioning
confidence: 99%
“…Neurophysiological and neuropsychological experiments show that the CNS-depressant medications impair an array of cognitive functions underlying [44][45][46][47] driving and other everyday activities . The cognitive effects include impaired visual [47][48][49][50][51] attention and reaction time , attentional 5 2 5 3 switching , planning and working 54 memory . In addition benzodiazepines cause a n t e r o g r a d e a m n e s i a a n d i n c r e a s e This has led to the problem which can berather ironically -referred to as 'driving under the influence of prescription medication'.…”
Section: O G N I T I V E To X I C I T Y O F S E D a T I V E P S Y Cmentioning
confidence: 99%